2019
DOI: 10.3390/ijerph16111990
|View full text |Cite
|
Sign up to set email alerts
|

Introducing of Online Channel and Management Strategy for Green Agri-food Supply Chain based on Pick-Your-Own Operations

Abstract: The popularity of e-commerce has impacted traditional retail business. Farmer cooperatives running green agri-food pick-your-own (PYO) farms are facing the choice of whether or not to adopt online channels. PYO operation refers to consumers picking and purchasing the agri-food growing on a farm, and due to it being environmentally-friendly, healthy, and popular, it has been widely adopted by many farm cooperatives. This paper aims to discuss the practicality of introducing online channels to already establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…The E-CLSCN model is constructed by using variational inequalities, and the sensitivity analysis is carried out by numerical examples. The conclusions of this paper are similar to the study of Zhao et al [12], that is, consumers' preference for products can effectively promote the profits of the corresponding node enterprises. However, this paper considers complex dynamic and static problems, so the results of this paper are more abundant than the study of Zhao et al [12].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The E-CLSCN model is constructed by using variational inequalities, and the sensitivity analysis is carried out by numerical examples. The conclusions of this paper are similar to the study of Zhao et al [12], that is, consumers' preference for products can effectively promote the profits of the corresponding node enterprises. However, this paper considers complex dynamic and static problems, so the results of this paper are more abundant than the study of Zhao et al [12].…”
Section: Discussionsupporting
confidence: 84%
“…The study of this paper from a dynamic and static perspective is more in line with the actual situation. Thirdly, the consumers' preference for products [2,15,16,[30][31][32][33], e-channel [11,12,14,34], the behavior of corporate promotion under the e-channel [19,20,[35][36][37][38], CLSCN [9,23,[44][45][46][47][48], are explored and then the above questions are combined to be studied, which has not yet been explored. Finally, inspired by the research of Seuring et al [40] and Shashi et al [41,42], the sustainable thinking is included in this paper, that is, considering the e-channel can effectively reduce the impact of the middlemen's behavior on the environment, and study the problem the E-CLSCN equilibrium.…”
Section: Supply Chain Considering Consumers' Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the freshness level function in period 2 is θ 2 = γhς, where γ ∈ (0,1) represents the discount factor of the freshness level in period two compared to period one. Then, similar to Zheng et al [28] and Hu et al [56], the utility functions of consumers in two periods are:…”
Section: Problem Descriptionmentioning
confidence: 95%
“…Moreover, some scholars also studied specific agri-food supply chains, including oranges, vegetable, cheese, fish, and dairy [15][16][17][18][19]. Given the special structure of agri-food supply chain, some other studies examined the optimal decisions of participants, such as "farmer and supermarket" [20], "farmer and company" [21], and "farm and consumers" [22]. In terms of research methods, Siddh et al [23] found that most of the current research focusing on the quality problems of fresh agricultural products was in the form of case studies and statistical analyses.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%